2014
DOI: 10.1016/j.geb.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Designing incentives for online question-and-answer forums

Abstract: In this paper, we provide a simple game-theoretic model of an online question and answer forum. We focus on factual questions in which user responses aggregate while a question remains open. Each user has a unique piece of information and can decide when to report this information. The asker prefers to receive information sooner rather than later, and will stop the process when satisfied with the cumulative value of the posted information. We consider two distinct cases: a complements case, in which each succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 22 publications
0
54
0
Order By: Relevance
“…In a game-theoretical analysis of social Q&A, Jain et al (2009) usefully distinguish between new answers that substitute for existing ones (providing an overall better answer alternative which renders existing answers redundant) and those that complement them (adding to and enriching the information already provided). Through a simulation exercise, they show that the existing voting system for Yahoo Answers is satisfactory in the case of substitution answers but less so for complementary answers.…”
Section: Quality In Social Q and Amentioning
confidence: 99%
See 1 more Smart Citation
“…In a game-theoretical analysis of social Q&A, Jain et al (2009) usefully distinguish between new answers that substitute for existing ones (providing an overall better answer alternative which renders existing answers redundant) and those that complement them (adding to and enriching the information already provided). Through a simulation exercise, they show that the existing voting system for Yahoo Answers is satisfactory in the case of substitution answers but less so for complementary answers.…”
Section: Quality In Social Q and Amentioning
confidence: 99%
“…(Paul, Hong et al, 2012). In addition to the possibility of distributing allocated upvotes amongst complementary answers (Jain, Chen et al, 2009) it has been suggested that voting on randomly presented samples of content might also alleviate this problem (Stray , 2009), though such an approach has yet to be field -tested.…”
Section: Redressing Voting Biasmentioning
confidence: 99%
“…In [29], Horton and Chilton investigated the relationship of wages and task difficulty, and proposed a model to estimate participants' reservation wage in crowdsourcing tasks. A number of reward and punishment mechanisms [40,46,57] have also been proposed to encourage users to provide quality contributions in the context of peer production systems. Lee et al [46], for example, introduced a voting-based reward mechanism for online Q&A forums, where not only the contributor of the winning answer but also the users who voted for the answer were rewarded.…”
Section: E Reward and Punishment Mechanismsmentioning
confidence: 99%
“…Also, creating a competitive environment where more contribution makes the user the top contributor of the category, this ensures higher rate of returning and contribution from the participants [13]. An approval-voting scoring rule and a proportional-share scoring rule can enable the most efficient equilibrium with complements information, under certain conditions, by providing incentives for early responders as well as the user who submits the final answer [6].…”
Section: Incentive Modelmentioning
confidence: 99%